About the role of the text transformation in the process of cyclization of an author’s book of verse (“Sumerki” by E. A. Boratynsky and “Prostoe, kak mychanie” by V. Mayakovky): О роли трансформации текста в процессе циклизации авторской поэтической книги («Сумерки» Е. А. Баратынского и «Простое как мычание» В. В. Маяков-ского) - Darvin, Mikhail; Moreva, Yuliya (Przegląd Wschodnioeuropejski, 2021)
In this paper the authors compare the two versions of the poetic dedication to P. A. Vyazemsky written by E. A. Boratynsky, the first one appeared in Pushkin’s “Sovremennik” magazine in 1836, the other one was published in Boratynsky’s book of verse “Sumerki” in 1842, and the untitled poem by V. V. Mayakovsky which appeared first in the book “Ya!” in 1913 and then in “Prostoe kak mychanie” in 1916. The transformations of the poems changed not only the meaning of the text but its function and played an important role in constructing of the artistic entity of the books. The authors pay attention not only to the minor changes of the text but also to the editorial and book printing details which are not less important for the meaning of the whole book.